Epidemiology and clinical relevance of mutations in postpolycythemia vera and postessential thrombocythemia myelofibrosis: A study on 359 patients of the AGIMM group. Issue 7 (11th May 2016) - Rotunno, Giada; Pacilli, Annalisa; Artusi, Valentina; Rumi, Elisa; Maffioli, Margherita; Delaini, Federica; Brogi, Giada; Fanelli, Tiziana; Pancrazzi, Alessandro; Pietra, Daniela; Bernardis, Isabella; Belotti, Clara; et al.
Abstract : Transformation to secondary myelofibrosis (MF) occurs as part of the natural history of polycythemia vera (PPV‐MF) and essential thrombocythemia (PET‐MF). Although primary (PMF) and secondary MF are considered similar diseases and managed similarly, there are few studies specifically focused on the latter. The aim of this study was to characterize the mutation landscape, and describe the main clinical correlates and prognostic implications of mutations, in a series of 359 patients with PPV‐MF and PET‐MF. Compared with PV and ET, the JAK2 V617F and CALR mutated allele burden was significantly higher in PPV‐MF and/or PET‐MF, indicating a role for accumulation of mutated alleles in the process of transformation to MF. However, neither the allele burden nor the type of driver mutation influenced overall survival (OS), while absence of any driver mutation (triple negativity) was associated with significant reduction of OS in PET‐MF, similar to PMF. Of the five interrogated subclonal mutations ( ASXL1, EZH2, SRSF2, IDH1, and IDH2 ), that comprise a prognostically detrimental high molecular risk (HMR) category in PMF, only SRSF2 mutations were associated with reduced survival in PET‐MF, and no additional mutation profile with prognostic relevance was highlighted. Overall, these data indicate that the molecular landscape of secondary forms of MF is different from PMF, suggesting that unknown mutational events might contribute to the progression from chronic phase disease to myelofibrosis. These findings also support more extended genotyping approaches aimed at identifying novel molecular abnormalities with prognostic relevance for patients with PPV‐MF and PET‐MF. Am. J. Hematol. 91:681–686, 2016. © 2016 Wiley Periodicals, Inc.